Factors influencing Colorado female secondary principals' leadership practices - Applewhite, Ann Simpson, author; Porter, Charles F., advisor; Paccione, Angela V., committee member; Banning, James H., committee member; Kennedy, Cathy, committee member (Colorado State University. Libraries, 2001)
The purpose of this study was to explore differences in leadership style attributes or traits of female secondary principals and the development of their styles through their stories. Twelve female secondary principals with three or more years experience in a site based managed school were nominated and interviewed using a semi-structured format. The intention was to discover whether or not female secondary principals developed feminine style attributes naturally as a result of socialization, or whether or not their styles developed as a result of workplace interactions with followers who expected them to use feminine style characteristics. The study also explored, through participants' stories, whether or not they encountered resistance when circumstances required them to use a more directive style of management often described as "masculine" and viewed as counter gender by most followers. Seven themes emerged as a result of data analysis. Three themes are related to job performance: Theme 1—Communication; Theme 2—Collaboration; and Theme 3—Gender Related Behavior. Three themes are related to job experience: Theme 4—Political Influence; Theme 5—Support; and Theme 6—Self Knowledge. Theme 7, Dissonance, overlaps the job performance and job experience areas. It describes the uncertainty and ambiguity the females in this sample encountered as they performed their tasks and as they experienced the principal's role. An analysis of their stories revealed that these women, indeed, experienced leadership differently. These female participants' stories revealed that using a characteristically feminine style was not necessarily natural. Rather, the sample in this research project was thoughtful and strategic in their use of leadership style traits. The project's importance is grounded in the pursuit of gender equality, a quest that continues twenty-nine years after the 1972 passing of Title IX of the Civil Rights Act of 1964. As leadership skills can be taught, the study points to a need to adjust leadership development classes can be adjusted to specifically address needs of females aspiring to the secondary principalship.
Keywords: school administration; secondary education; educational administration